2022
DOI: 10.1101/2022.10.31.22281757
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Digital tools to improve parenting behavior in low-income settings: A mixed-methods feasibility study

Abstract: Introduction: Digital parenting interventions could be potentially cost-effective means for providing early child development services in low-income settings. This 5-month mixed-methods pilot study evaluated the feasibility of using Afinidata, a comprehensive FBMessenger-based digital parenting intervention in a remote rural setting in Latin America and explored necessary adaptations to local context. Methods: The study was conducted in three provinces in the Cajamarca region, Peru, from February to July 2021.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(24 reference statements)
0
0
0
Order By: Relevance
“…Additionally, as the population group is low-income families, issues related to digital interventions causing inequalities or a divide in the population need to be considered. While some studies exist which have found that low-SES families still have high access to smartphones [76], there is a lack of understanding in the current papers as to whether there were any limitations to accessing digital devices or whether developing digital interventions could result in widening inequality in relation to engagement within public health interventions [74].…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 91%
“…Additionally, as the population group is low-income families, issues related to digital interventions causing inequalities or a divide in the population need to be considered. While some studies exist which have found that low-SES families still have high access to smartphones [76], there is a lack of understanding in the current papers as to whether there were any limitations to accessing digital devices or whether developing digital interventions could result in widening inequality in relation to engagement within public health interventions [74].…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 91%